(untitled) (Swiss Medical Weekly, 2015)
QUESTIONS UNDER STUDY: Optimal oxygen saturation (SpO2) targets for extremely low gestational age neonates (ELGANs, gestational age [GA] <28 weeks) are unknown. Conflicting results from five recently published multicentre trials, which randomised ELGANs to high (91 to 95%) or low (85 to 89%) SpO2 targets from birth up to a corrected GA of 36 weeks, prompted us to examine our experience with two different SpO2policies. METHODS: We retrospectively compared outcomes of two cohorts of ELGANs which were exposed to two different SpO2 target policies adapted to the infants’ corrected GA. Between 1 January 2000 and 30 June 2007, SpO2 targets were 85 to 95% at <30 weeks and 88 to 97% at ≥30 weeks (high SpO2 target cohort, n = 157). Between 1 July 2007 and 31 December 2011, SpO2 targets were lowered to 80 to 90% at <30 weeks, 85 to 95% between 30 and 34 weeks and finally 88 to 97% at ≥34 weeks (low SpO2 target cohort, n = 84). RESULTS: There were no statistically significant differences between the high and low SpO2 target cohorts in mortality rates (15.9 vs 17.9%, risk ratio [RR] 0.89; 95% confidence interval [CI] 0.50–1.60), incidences of severe retinopathy of prematurity (2.3 vs 0%, RR 3.68; 95% CI 0.19–70.3), or moderate/severe bronchopulmonary dysplasia (14.4 vs 21.1%, RR 0.68; 95% CI 0.37–1.26). CONCLUSIONS:Adapting SpO2 targets to the advancing corrected GA seems safe and is associated with low incidences of short-term complications. Mortality rates did not vary with the two different SpO2 target policies utilised and were comparable to those reported from recently published randomised controlled SpO2 target trials.